The survey on type of method that used in controlling the beetles in rice storage in Melaka Tengah, Melaka / Fatin Nurul Atira Mohd Ayob and Nur’amira Hamid - Mohd Ayob, Fatin Nurul Atira; Hamid, Nur’amira (Faculty of Plantation and Agrotechnology, 2018)
Oryza sativa L. rice is the most important food crop of the developing world and the staple food of more than half of the world's population. It rich in nutrients and vitamins and minerals. Stored-product insects pest are the pest that attack agricultural commodities during storage, processing, and distribution. Sitophilus oryzae and Tribalium castaneum is a major insect pest that damage the rice quality and cause yield losses. The objective of this research are to identify the types and favourable methods use in controlling beetles in rice storage, in this studies, 10 rice mills and smallholders in Melaka Tengah, Melaka area were involved in collecting data about types of method that company used in rice storage to control the insect pest infestation. In controlling the rice beetles, there are many methods can be used such as physical and mechanical method, chemical method, cultural control, insect growth regulators, biological control, microbial control, natural plant products and essential oils. Nevertheless, most of the company used chemical method because of the level of effectiveness and fast. This research was suggested to the company to used more than one method in controlling the infestation of rice beetles.